Unlocking the potential of predictive maintenance for intelligent manufacturing: A~case study on potentials, barriers, and critical success factors - Marcel André Hoffmann; Rainer Lasch (Schmalenbach Journal of Business Research (SBUR), 2025)
Predictive maintenance (PdM) is a~data-driven maintenance strategy that aims to avoid unplanned downtimes by predicting the remaining lifetime of maintenance objects. Thus, unnecessary replacements of spare parts and critical process disturbances due to breakdowns can be avoided. Despite the widely recognized advantages of this technology, the number of successful applications in practice is still very limited. Our study aims to address the theory-practice gap by conducting a~comprehensive case study involving 15~expert interviews with industry professionals to uncover critical factors that hinder the successful implementation of PdM. Our findings shed light on the underlying reasons for a~hesitant PdM implementation, including challenges related to digital readiness, data quality and accessibility, technological integration, and maintenance organization. By providing an in-depth analysis of these factors, our study offers valuable insights and guidelines to improve the implementation success rate of PdM in the industrial context. Based on the empirical findings, we present critical implementation factors and develop a~framework with ten propositions that aim to dismantle barriers in the industrial application process of PdM and stimulate further research in academia.
Keywords: L60; O14; O32; 650; Case study; Condition monitoring; Digitalization; Implementation; Industry~4.0; Predictive maintenance; Success factors